Intergenerational high-fat diet impairs ovarian follicular development in rodents: a systematic review and meta-analysis - Paula, Verônyca G [UNESP]; Vesentini, Giovana [UNESP]; Sinzato, Yuri K. [UNESP]; Moraes-Souza, Rafaianne Q. [UNESP]; Volpato, Gustavo T.; Damasceno, Débora Cristina [UNESP] (Oxford University Press (OUP), 2022)
CONTEXT: Excessive consumption of high-fat diets has increased in the population over time and is harmful to female fertility. OBJECTIVE: To investigate and discuss the effects of a high-fat diet on ovarian follicles in rodents. DATA SOURCE: A systematic literature search of PubMed, EMBASE, Web of Science, and SCOPUS was carried out. DATA EXTRACTION: Study characteristics, including study design, population, intervention, outcome, and risk of bias were analyzed. DATA ANALYSIS: Twenty-two articles were included in a systematic review. Given the availability of studies, a quantitative meta-analysis included 12 studies that were performed for outcomes. There was a decrease in primordial follicles in female rodents that received a high-fat diet compared with the standard diet group. The offspring of mothers exposed to a high-fat diet showed an increased number of cystic follicles and a decreased number of secondary follicles and antral follicles, compared with the control diet group. Therefore, these high-fat diet-induced follicular alterations might impair the fertility of dams and their female newborns. CONCLUSION: The consumption of a high-fat diet causes damage to ovarian follicular development, and this commitment will persist in the next generation. SYSTEMATIC REVIEW REGISTRATION: PROSPERO registration no. CRD42019133865.
Keywords: corpora lutea; cysts; maternal diet; mouse; ovary; rat